Dependence of microstructural, mechanical and electrical properties on growth rates in directional solidified Zn-Al-Bi eutectic alloy - Karamazi, Yasin; Bayram, Umit; Ata, Pinar; Aksoz, Sezen; Keslioglu, Kazim; Marasli, Necmettin (ELSEVIER, 2016)
Zn-5%Al-0.2%Bi (mass fraction) alloy was directionally solidified upward at a constant temperature gradient with a wide range of growth rates using a Bridgman-type directional solidification furnace. The eutectic spacings, microhardness, ultimate tensile strength and electrical resistivity for directionally solidified Zn-Al-Bi alloy were measured. Dependence of eutectic spacings, microhardness, ultimate tensile strength and electrical resistivity on growth rates was obtained by linear regression analysis. The results obtained in the present work for low growth rates (smaller than 450.0 mu m/s) are in good agreement with experimental results obtained in previous work for directional solidified Zn-Al eutectic alloy with a similar growth rate but differs from the Jackson-Hunt eutectic theory and those obtained in previous experimental works at higher growth rates. The critical growth rate might be 450.0 mu m/s for the Zn-Al-Bi eutectic alloy. From the plot of heat flow versus temperature, enthalpy of fusion, specific heat difference between liquid and solid phases and melting temperature for the Zn-Al-Bi alloy are found to be 112.55 J/g, 0.291 J/(g.K) and 660.20 K, respectively.
Keywords: directional solidification; zinc-aluminum alloy; microstructure; microhardness; tensile strength; electrical properties; CORROSION-RESISTANCE; CU-AG; MICROINDENTATION HARDNESS; TEMPERATURE-GRADIENTS; RAPID SOLIDIFICATION; THERMAL PARAMETERS; LAMELLAR SPACINGS; HEAT-TREATMENT; SN-ZN; PB-CD; Metallurgy & Metallurgical Engineering